Transadapting fable into a parable for Indonesian Muslim children: Strategies and impacts - SF. Luthfie Arguby Purnomo; Lilik Untari; SF. Lukfianka Sanjaya Purnama; Muhammad Zainal Muttaqien; Robith Khoiril Umam; Yustin Sartika; Muh Nashirudin; Shabrina An Adzhani (Universitas Pendidikan Indonesia, 2022)
The demand for domestication and localization of children’s literature compels translators to not only translate the texts but also transadapt them. Significant problems arise when the texts have to fit the cultures and religions of the target users. This qualitative study attempts to address this issue. Gathering teachers of Taman Pendidikan Al Qur’an (TPQ) or Qur’an study club for Muslim children in the Greater Boyolali area of Indonesia, children’s literature translators, and TPQ students in a Focus Group Discussion, we investigated the strategies of transadapting fables in English into Bahasa Indonesia with Islamic values as the core teaching along with the impacts ensued. Through the FGD constructed based on the purification strategy by Klingberg (1986), translation as adaptation and selection by Gengshen (2003), children picturebook translation by Oittinen (2000), narrative connectedness by Christman (2004), proairetic decoding by Nikolajeva (2010), and skopos by Reiss and Vermeer (2014), paratextualization, insertion, and bleaching strategies are constructed. Paratextualization adds clickable religious comments on the digital versions of the fables. Insertion adds religious lessons within the text. Bleaching refines any expressions considered unfit for the target religious values. These strategies trigger an impact called drifting. To reveal the extent of faithfulness, we constructed a drifting-level assessment. This assessment enables translators to reveal whether a transadapted children’s literature is still on track, slipped, or out of track. The study finding is expected to fill up the theoretical absence of transadaptation strategies and drifting level assessment. Its practical nature also brings benefits for children’s literature translators and TPQ teachers.